2016
DOI: 10.1016/j.scitotenv.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the benefits of improved marine environmental quality under multiple stressors

Abstract: Many marine ecosystems are under increasing pressure from multiple stressors. In the Baltic Sea, these stressors include oil and chemical spills from shipping, nutrient run-off from land and the introduction of non-indigenous species. All of these pressures have been growing over recent years. Increasing pressures lead to reductions in environmental quality, which produce negative effects on human well-being. In this paper, the choice experiment method is used to estimate the benefits to people in Estonia resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Numerous studies have evaluated the WTP for improving the quality of water bodies (e.g., García-Llorente et al, 2012;Doherty et al, 2014;Ahtiainen et al, 2013, Hanley at al., 2015, Tuhkanen et al, 2016, Pakalniete et al, 2017. Considering the poor chemical and ecological state of the Oka river estuary and the Gernika aquifer (Gobierno Vasco, 2004), which also affect bathing waters, high WTP for improving water quality comes as no surprise.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have evaluated the WTP for improving the quality of water bodies (e.g., García-Llorente et al, 2012;Doherty et al, 2014;Ahtiainen et al, 2013, Hanley at al., 2015, Tuhkanen et al, 2016, Pakalniete et al, 2017. Considering the poor chemical and ecological state of the Oka river estuary and the Gernika aquifer (Gobierno Vasco, 2004), which also affect bathing waters, high WTP for improving water quality comes as no surprise.…”
Section: Resultsmentioning
confidence: 99%
“…Which ecosystem state provides which services, and which pressures impact the states and the potential underlying ecosystem services). In ecosystem approach studies to determine the costs of degradation studies (Pakalniete et al, 2013;Tuhkanen et al, 2015) the link between the ecosystem state and the provided services is not known.…”
Section: Figure 35 Ebm-dpser Conceptual Model: Ecosystem Services Inmentioning
confidence: 99%
“…For each study is indicated to which GES descriptor the study is related. Three studies focus explicitly on all main concerns with respect to reaching GES in a country, the Latvian study (Pakalniete et al, 2013), the Estonian study (Tuhkanen et al, 2015) and the UK study (HMGovernment, 2012a;2012b). These studies are explained in a bit more detail in this paragraph.…”
Section: Studies Assessing Welfare Effects Of Reaching Gesmentioning
confidence: 99%
See 2 more Smart Citations